Visceral Injury in Abdominal Trauma: A Retrospective Study - Leite, Sara (2013)
Background: Abdominal trauma is a major cause of morbi-mortality all over the world which makes it essential an approach focused on rapid diagnosis and treatment. The main goals of this study are to identify global epidemiologic data of abdominal trauma in our tertiary trauma center and to study traumatic lesions, treatment and outcome.Material and Methods: Retrospective analysis of the clinical file of all patients admitted with abdominal trauma, over a period of 5 years, in a tertiary trauma center.Results: the total mean of ages was 42.6 years and the male gender was the most affected (74.2%). At admission, most patients had a Revised Trauma Score > 4. The mainly causes of trauma were blunt from motor-vehicle collisions (39.9% as motor-vehicle occupant and 10.7% from pedestrian collisions) and falls (25.5%). Penetrating trauma, by abdominal stab wounds and gunshot wounds, occurred only in 12.3% of the cases. Hollow visceral injuries were more frequent in that context. In 19.5% of the cases multiple abdominal organinjury occurred. Conservative treatment was performed in 65.3% of the cases. Global mortality was 12%, being null after penetrating lesions.Conclusions: Abdominal trauma, more frequently, is the result of motor-vehicle crashes and falls, being blunt in the majority of the cases. The most affected organs are solid and the approach is conservative. Hollow visceral lesions continue to be of difficult diagnose.